Levels of inflammatory cytokines in patients with different phenotypes of heart failure - Liudmila, Kalatsei; Mathotaarachchi, Bihara Rasanjalee; Hewage, Sandeepa Abhishek; Jayasinghe, J. A. Sudeepa Madhavi Rajakaruna; Kavinda Nuwan, Wadu Arachchige (International Journal of Research in Medical Sciences, 2025)
Background: The association between HF and inflammation was first recognized in 1990 by Levine et al, who reported elevated levels of TNF in patients with HFrEF. To date, the levels of C-reactive protein, interleukin 6, and interleukin 1-beta are verified to be increased in plasma of HF patients. Current clinical trials are investigating on the effectiveness of IL-1 blockade to reduce inflammation, ventricular remodeling, and improved exercise capacity in patients with HF. Methods: The study included 76 patients with HF of NYHA functional classes I-IV. 46 (61%) patients had a preserved LVEF (≥50%) and 30 (39%) had reduced LVEF (<50%). All patients underwent clinical, laboratory, and instrumental studies, including determination of CRP and IL-1 levels in venous blood serum using enzyme immunoassay. Statistical analysis was performed using the STATISTICA 12.0 software. Results: Patients with HFrEF more often suffered from atrial fibrillation than patients with HFpEF. Also, patients with HFrEF were characterized by higher HF NYHA class. Patients with HFrEF had significantly higher levels of BNP and NT-proBNP. When conducting an enzyme immunoassay in patients of the HFrEF group, the CRP level was 3.95 mg/L, and in patients of the HFpEF group -3.52 mg/L, these differences were statistically significant (p=0.011). However, there were no intergroup differences in IL-1 level. Conclusions: Patients with HFrEF had higher values of CRP (p<0.05) in comparison with patients with HFpEF. However, there were no intergroup differences in IL-1 values (p>0.05). Reliability of the obtained results should be further checked on larger samples of patients.